(untitled) (Indian Journal of Child Health, 2020)
Background: Neonatal hyperbilirubinemia (NH) is the most common cause of readmission during the early neonatal period. There is a need to find the methods of screening babies at higher risk of developing jaundice before discharge. Objectives: The objectives of this study were to find out the predictive value of cord serum albumin (CSA) levels as an indicator of neonatal jaundice. Materials and Methods: A cross-sectional study conducted at a tertiary hospital of Maharashtra, from October 2017 to September 2019 on 410 term newborns. CSA was collected at birth and correlated with serum bilirubin levels collected at 48 h of life. Statistical analysis was performed and the sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) with a 95% confidence interval obtained. Results: Of 410 cases, 266 (64.8%) developed clinical jaundice, of which 148 (93.6%) had albumin levels <2.8 g/dl, 79 (74.5%) between 2.8 and 3.3 g/dl, and 39 (26.7%) >3.3 g/dl. At CSA level <2.8 g/dl, the sensitivity of 93.67% with PPV and NPV of 51.57% and 94.65%, respectively, was found. At CSA level 2.8–3.3 g/dl, the sensitivity estimated was 85.98% with a PPV and NPV of 85.34% and 74.31%, respectively. Conclusion: In this study, CSA appears to be a risk indicator in predicting neonatal hyperbilirubinemia. CSA level <2.8 g/dl is a high-risk factor for the future development of neonatal hyperbilirubinemia, while those with CSA level >3.3 g/dl are probably safe for early discharge from the hospital.